(untitled) (Sains Humanika, 2024)
Differentiated Instruction (DI) is a comprehensive approach that addresses a variety of students’ requirements and needs in a classroom environment, including their interests, readiness, and learning styles. The idea behind this approach is based on the belief that every classroom is unique. Thus, educators should review and modify their teaching practice from time to time. Hence, this study aims to identify the learning methods in differentiated instruction, their advantages, and challenges to implement in chemistry education using qualitative methods through semi-structured interviews. Seven secondary school teachers with 10 years of teaching experience in Chemistry were selected purposely for this study. To achieve the research objectives, thematic analysis is used, involving reading through the data and analyzing them according to the themes. The experts validate the updated questioning instrument prepared by the researchers to ensure the validity of the questionnaire. Findings reveal that most of them have specific experiences of using differentiated pedagogy to teach chemistry. Three of them described that students, who tend to master visual-spatial intelligence, can interpret and enhance their understanding of a chemistry concept through drawing, namely for the formation of ionic bonds and covalent bonds. For students, who master linguistic-verbal intelligence, teachers can use presentation activities to enhance their understanding of the chemistry concept. Hence, it can promote active learning, encourage students to ask questions, increase students’ confidence level in performing classroom activities and other advantages. Conversely, the difficulty faced by the teachers in implementing DI is time constraint. Hence, differentiated instruction is a valuable and practical approach to addressing the diverse needs of students, promoting engagement, collaboration, and the development of essential skills for lifelong learning. Integrating DI principles can contribute significantly to creating enriching and effective learning environments as education evolves.